Central unilocular mucoepidermoid carcinoma of the mandible: A case report and literature review - Arezoo Aghakouchakzadeh; Neda Kargahi; Shirin Shahnaseri; Salman Shakeri (Wolters Kluwer Medknow Publications, 2019)
Mucoepidermoid carcinoma (MEC) is the most common salivary gland malignancy. Central MEC (CMEC) is a rare tumor which affects women more than men and is more common in the mandible. Most cases are histologically classified as low-grade tumor and radiographically appear as well-defined unilocular or multilocular radiolucent lesion, although this tumor causes destruction and metastasis to other organs. In this article, we present a rare case of CMEC in a 47-year-old woman with unilocular radiolucent lesion of the mandible. Early and accurate diagnostic approach in all lesions with clinical/radiographical bland appearance is important, and all possibilities such as a malignant lesion should be considered.